The Impact of Polyphenols-Based Diet on the Inflammatory Profile in COVID-19 Elderly and Obese Patients - Santos, Juliana Carvalho; Ribeiro, Marcelo Lima; Gambero, Alessandra (Frontiers in Physiology, 2021)
The World Health Organization declared the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-associated disease (coronavirus disease 2019 – COVID-19) as a pandemic in March 2020. COVID-19 is characterized by cytokine storm, acute respiratory distress syndrome (ARDS), and systemic inflammation–related pathology and already kills more than 1.5 million of people worldwide. Since aged and obese COVID-19 patients exhibit an enhanced inflammatory status, they represent a high-risk cluster for rapidly progressive clinical deterioration. These individuals present comorbid disorders and immunosenescence that may promote viral-induced cytokine storm and expression of molecules acting as virus receptor as angiotensin I converting enzyme 2 (ACE2) and CD26 (dipeptidyl-peptidase 4), resulting in respiratory failure and increased morbidity and mortality. A better knowledge of SARS-CoV-2 infection in inflammatory-associated high-risk population is essential in order to develop the therapies needed to combat or prevent severe COVID-19. Here, we review the pathogenesis and clinical implications of inflammatory disorders and disease markers associated to senescence in COVID-19 patients and the emerging evidence to argue that a high intake of polyphenols may have a protective effect on SARS-CoV-2 illness severity.